The determinants of poverty in the West Papua province - Pentury, Marthen Anthon (Universitas Muhammadiyah Yogyakarta, 2023)
Poverty has become a serious development problem, including in West Papua Province. This research has become a fundamental issue because West Papua tends to be difficult to get out of poverty problems, which has the second-highest percentage of poverty in Indonesia. This study aims to analyze the determinants of poverty in West Papua. The dependent variable is poverty, and the independent variables are population density, unemployment, human development index, and the average length of schooling. This research uses multiple regression analysis time series, 11 years period. The finding of this study is that unemployment has a positive and significant effect on poverty. Meanwhile, the human development index and the average length of schooling have a negative and significant effect. The implication is that the human development index and the average length of schooling must be expanded in scope to open access to people living in remote areas. The region's characteristics and the population tend to live in the interior, so accessibility is an important factor in alleviating poverty in West Papua.